Democracy, Deliberation, and Education - Asen, Robert, 1968- (Rhetoric and democratic deliberation., 2015)
"Explores the ways that school board members engage each other to make decisions for their local communities in the United States. Illustrates the perils and promise of local policymaking as people seek to chart a future course for their communities, addressing issues of ideology, scarcity, expertise, and trust"--Provided by publisher.